Burden of care and coping strategies among informal caregivers of people with behavioral and psychological symptoms of dementia in rural south-western Uganda - Owokuhaisa, Judith; Kamoga, Ronald; Musinguzi, Pius; Muwanguzi, Moses; Natukunda, Sylivia; Mubangizi, Vincent; Asiime, Keith; Rukundo, Godfrey Zari (BMC Geriatrics, 2023)
Background: Caregiving is a draining role that inflicts a significant level of burden upon caregivers for older people with Behavioral and Psychological Symptoms of Dementia (BPSD). Caregiver burden is associated with poor health outcomes for both the people with BPSD and their caregivers. This study explored the burden of care and coping strategies used by informal caregivers of older people with BPSD in rural Southwestern Uganda. Methods: This was a qualitative study among informal caregivers of older people with BPSD in Rubanda and Rukiga districts. We conducted in-depth interviews with a purposive sample of 27 caregivers using an interview guide. The interviews were conducted in the local language, audio recorded, transcribed, translated into English, and thematically analyzed. Results: There were two major themes: caregiver burden and coping strategies. Caregiver burden was described as financial, physical, psychological and social. Caregivers mainly used emotion-focused coping strategies (religious coping, acceptance and emotional support seeking). Problem-focused coping strategies (planning) and dysfunctional coping strategies (self-distraction) were used to a lesser extent. Conclusion: Informal caregivers of people with BPSD adopted both emotional and problem-focused coping strategies to cope with the burden of care for people with BPSD. Such coping strategies seemed to lighten the burden of caring, in the long motivating the caregivers to continue with the caring role.
Keywords: Caregiver; Burden; Coping strategies; Behavioral and psychological symptoms of Dementia